2007
DOI: 10.1007/s10792-007-9031-3
|View full text |Cite
|
Sign up to set email alerts
|

Clear corneal incision leakage after phacoemulsification––detection using povidone iodine 5%

Soon-Phaik Chee

Abstract: The purpose of this work was to study the incidence of clear corneal wound leakage at the conclusion of standard co-axial phacoemulsification in a prospective observational series of 100 consecutive cataract cases in a single surgeon's institutional practice. At the conclusion of standard co-axial phacoemulsification using a 2.75 mm temporal single plane clear corneal incision with a 1 mm clear corneal side-port incision, the wounds were hydrated and checked for water-tightness. Povidone iodine 5% (P-I) was th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
18
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 11 publications
1
18
0
Order By: Relevance
“…In addition, it has been shown that multiple instrument insertions and excessive manipulation may distort the incisions, thereby increasing the likelihood of inflow and/ or leakage during the postoperative period (8) . Chee et al demonstrated a high incidence of side port incisions leakage after phacoemulsification (9,10) . Such leakage may lead to bacterial contamination and thus potentially to infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has been shown that multiple instrument insertions and excessive manipulation may distort the incisions, thereby increasing the likelihood of inflow and/ or leakage during the postoperative period (8) . Chee et al demonstrated a high incidence of side port incisions leakage after phacoemulsification (9,10) . Such leakage may lead to bacterial contamination and thus potentially to infection.…”
Section: Discussionmentioning
confidence: 99%
“…Chee et al performed intraoperative stromal hydration in an attempt to seal leaking incisions. However, they observed that if the incision was overly manipulated, leakage persisted regardless of the hydrosealing (9) . Moreover, the hydrosealed wound is more susceptible to local Descemet membrane detachment than without hydration 18 .…”
Section: Discussionmentioning
confidence: 99%
“…1 We describe a technique for effectively sealing a clear corneal wound with subsequent confirmation of a watertight seal.Clear corneal phacoemulsification is performed under topical anesthesia, and surgical ports are hydrated. If the wound is leaky, an air bubble is injected into the anterior chamber through the side port so the bubble's diameter is one third to one half the corneal diameter.…”
mentioning
confidence: 99%
“…1 We describe a technique for effectively sealing a clear corneal wound with subsequent confirmation of a watertight seal.…”
mentioning
confidence: 99%
See 1 more Smart Citation